A Contingência dos caminhos: Verdade e redescrição em Richard Rorty - Souza, Roger Klinsman Aguiar de (2019)
The present research aims to examine the main features of Richard Rorty's theory of truth. Rorty's pragmatism can be understood as a counterpoint to theories that purport to establish a foundational-representationalist relationship between language and the world, in which the mind behaves as a mirror capable of representing reality accurately. Based on his anti-foundationalism, Rorty proposes not a strong theory of truth, but a typology of descriptive character capable of satisfying the use we make of the term "true" in the practical-communicational scope. In this sense, its typology has a deflationary and strictly negative aspect, since it does not seek a definition of the nature of truth nor does it seek a representation of this having as a background the traditional subject-object duality, namely, the cognoscent and the known. Our author's proposal is to make philosophy remain in the field of contingency, that is, in the contextual-historical context, always open to new descriptions and, consequently, adept of new worlds and new languages.